UPAYA MENINGKATAKAN KREATIVITAS SISWA DALAM PEMBELAJARAN BAHASA INDONESIA MENGGUNAKAN MODEL PEMBELAJARAN KONSTRUKTIVISME - Shenia Cahyawati Ananstasia; Cerianing Putri Pratiwi; Erna Agustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to enhance students' creativity in Indonesian language learning at SDN 01 Demangan by implementing a constructivist learning model. This research employs a classroom action research method with a qualitative approach, conducted over two cycles. In the first cycle, the teacher designed and applied a constructivist learning model comprising five stages: activation of prior knowledge, exploration, restructuring, application, and reflection. The results of the first cycle indicated that while the implemented model was clear and structured, there were shortcomings in the creativity of activities and support for students who faced difficulties. In the second cycle, the teacher revised the learning model by adding more creative activities, allowing more time for students, and using diverse assessments. Findings from the second cycle showed a significant increase in student creativity, with more creative and original works. This study confirms that a constructivist learning model, when effectively applied, can enhance students' creativity in Indonesian language learning, with the note that ongoing adaptation and improvement by teachers are necessary. The study provides recommendations for improving the planning and implementation of a more creative and diverse learning model to maximize students' creative potential.